Beautiful nights : a novel [large type] - George, Nina, 1973- (Randon House Large Print Publishing, 2025)
"Respected Parisian behavioral biologist Claire has become increasingly desperate to feel that she is still alive and not just functioning. Julie is waiting for something that will set her on fire inside--the rush of life, colors, courage and passion. A summer in Brittany brings the two different women together. Under the blazing sun, in the endless silence of the sea and in the raging storm of a nightthunderstorm, they rediscover joy of life, femininity and passion -and will never be the same again."--Provided by publisher.